INNOVATION OF ISLAMIC EDUCATION TEACHING METHODS BASED ON ICT IN SECONDARY SCHOOLS - Ruslan, Muhammad (Proceeding International Seminar of Islamic Studies, 2024)
This article discusses the Innovation Of Islamic Education Teaching Methods Based On Ict In Secondary Schools. The method used in this article is a literature review method, derived from literature with facts obtained from the field. The data or materials are sourced from the library, including books, journals, articles, and so on. Data sources are also gathered by collecting literature sources to obtain theoretical information and explanations. The data analysis technique involves summarizing, presenting data, and drawing conclusions. Innovative learning methods can stimulate students to actively participate in the learning process, thereby improving the overall quality of education. The digital era demands the need for teachers' creativity, such as using various innovative methods, to prevent their roles from being replaced by rapidly advancing technology. Some learning methods that can be used to support innovative learning include flipped learning, blended learning, and e-learning.